2017
DOI: 10.3390/ijerph14111341
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Epidemiological Trends of Acute Gastroenteritis Associated with Noroviruses in China from 2006 to 2016

Abstract: There are periodical norovirus-associated acute gastroenteritis outbreaks around the world. This study aimed to analyze the molecular and epidemiological features of norovirus infections in China during 2006–2016. We extracted epidemiological data from 132 norovirus outbreaks and the norovirus genotyping for 1291 sequences in China over the past ten years. A total of 132 norovirus outbreaks (8133 cases) were reported in China, where the east and south regions were most affected [47.7% (63/132)]. The highest nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 49 publications
5
38
0
Order By: Relevance
“…GII.4/Sydney 2012 was first identified in Australia, France, and New Zealand, and subsequently isolated in the United States, Belgium, Denmark, Scotland, Japan, and China. Of note, after 2012, the GII.4/Sydney 2012 variant was the dominant epidemic strain in Hohhot and most other regions of China, both in sporadic NV cases and NV outbreaks [19,21]. Previous studies show GII.4 usually caused epidemics in adult populations, whereas GII.3 NV was prevalent in young children and infants [45,46].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…GII.4/Sydney 2012 was first identified in Australia, France, and New Zealand, and subsequently isolated in the United States, Belgium, Denmark, Scotland, Japan, and China. Of note, after 2012, the GII.4/Sydney 2012 variant was the dominant epidemic strain in Hohhot and most other regions of China, both in sporadic NV cases and NV outbreaks [19,21]. Previous studies show GII.4 usually caused epidemics in adult populations, whereas GII.3 NV was prevalent in young children and infants [45,46].…”
Section: Discussionmentioning
confidence: 96%
“…Three major clusters (I-III) and five smaller genetic lineages (A-E) have been identified in the VP1 region of GII.3 NV [13,18]. Global surveillance data over the years indicated that the majority of outbreaks of NV were caused by GII.4, but the recent NV outbreak strains in Asia were GII.2 and GII.17 [1,19,20]. Furthermore, other genotypes were co-circulating, with different epidemiological patterns in different regions [1,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…No other norovirus outbreaks were reported in Beijing during the same period ( specific population : 1 point). Schools are a common site for norovirus outbreaks in China (Qin et al., ), so we scored the criterion “ geographic distribution ” as 0 points. More than 80% of cases had vomiting, nausea, and stomach pain, which were the typical symptoms of norovirus infection, no matter if it was intentionally or unintentionally caused ( clinical manifestation : 1 point).…”
Section: Resultsmentioning
confidence: 99%